MANAGEMENT OF QUR'AN LEARNING IN IMPROVING STUDENTS' TAHSIN IN PESANTREN; UMMI PERSPECTIVE METHOD - Fawaid, Achmad; Diana, izzah (Managere: Indonesian Journal of Educational Management, 2022)
This study analyses the management of learning the Qur'an through the Ummi approach at Islamic boarding schools. This study uses a descriptive qualitative research method. Data collection techniques in this study are through interviews, observation, and documentation studies. The results of the study show: 1) The planning starts with teacher certification, determine the learning model, and prepares teaching materials (materials) and stages of learning using the Ummi method. 2) The implementation, carried teacher, outdoes teacher discipline, fostering student enthusiasm, facilities, adequate media sources, filling in teacher and student absences and a complete assessment journal. 3) Evaluation, namely the implementation of the exam as a form of completion in learning.